Harmonization of Religious Values and Customs of the Banua Tribe in Batu-Batu Gunung Tabur, Berau - Emilia Nurwati; Khamam Khosiin; Benny Prasetya (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the harmonization of religious values and customs among the Banua Tribe in Batu-Batu Gunung Tabur, Berau. The research focuses on how religious values and local customs are practiced, negotiated, preserved, and transmitted within the community. This study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving customary leaders, religious leaders, elders, youth, and community members. The findings show that Banua customs function not only as cultural heritage, but also as a medium for internalizing Islamic values. Traditions such as Puncak Rasul, Betarbangan, Hadrah, collective prayer, deliberation, and mutual assistance contain values of gratitude, ukhuwah, respect, responsibility, tolerance, and social solidarity. The harmonization process occurs through social negotiation between customary leaders, religious leaders, families, and young people. This process allows adat to remain culturally meaningful while staying aligned with Islamic principles. However, modernization creates challenges for cultural regeneration, especially through declining youth participation, changing lifestyles, digital influence, and weak intergenerational transmission. The study concludes that Banua customs contribute to Islamic education by functioning as a social curriculum based on local wisdom. The findings highlight the need to strengthen adat-religion dialogue, involve youth in cultural practices, document local traditions, and integrate Banua local wisdom into Islamic education and regional cultural programs.